This teacher [videorecording (DVD)] - Jackson, Mark, 1971-; Herzi, Hafsia; Kazemy, Sarah, 1987-; Walters, Lucy (Actor); Kane, Kevin (Actor) (Breaking Glass Pictures, 2020)
A French Muslim woman travels to New York City to visit her childhood best friend from Paris. When the reunion proves disastrous, Hafsia steals her friend's credit card and identity, and disappears to a remote cabin upstate. Deep in the woods and alone for the first time in her life, she experiences a divine revelation of an existence without borders. When she discovers that she's not alone, Hafsia's sojourn in nature gradually descends into a terrifying study of an Islamophobic America.